Effect of home care visits on the quality of life of the elderly with hypertension in the health center area - Hijrah Hijrah; Nur Syamsi Norma Lalla (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: Hypertension is a major public health concern among the elderly, contributing significantly to morbidity, mortality, and reduced quality of life. Home care visits represent a community-based approach to enhance disease management, promote treatment adherence, and improve well-being among older adults. This study aimed to evaluate the effect of home care visits on the quality of life (QoL) of elderly individuals with hypertension in a primary health center area. Methods: A quasi-experimental pre–post design with a control group was conducted involving 100 elderly participants diagnosed with hypertension. The intervention group received structured home care visits conducted by community nurses over a period of eight weeks, focusing on health education, medication adherence, diet modification, blood pressure monitoring, and lifestyle counseling. The control group received standard outpatient care. Quality of life was assessed using the WHOQOL-BREF instrument, and blood pressure measurements were recorded at baseline and post-intervention. Data were analyzed using paired t-tests and ANCOVA to compare changes between groups. Results: The results showed a significant improvement in the mean QoL score of the intervention group (from 56.3 ± 7.5 to 68.7 ± 6.8; p < 0.001), particularly in the physical and psychological domains. Mean systolic blood pressure decreased by 11.4 mmHg and diastolic by 6.8 mmHg (p < 0.05). No significant change was observed in the control group. Conclusion: Regular home care visits effectively enhance the quality of life and blood pressure control among elderly patients with hypertension. Integrating home-based nursing interventions within primary health services can promote holistic, continuous care and support aging-in-place initiatives.